PENGEMBANGAN MACROMEDIAFLASH 8 PROFESSIONAL BERBASIS KARAKTER CINTA TANAH AIR SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU BAGI SISWA KELAS IV SD - Dewi Prabasari; Vera Yuli Erviana (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
The aim of this study; 1) to find out the steps to develop MacromediaFlash 8 Professional Based on the Character of Love of the Motherland in My Cultural Diversity Subtema for 4th grade students; 2) To find out the feasibility of MacromediaFlash 8 Professional Based on Land Love; 3) To find out student responses and teacher assessments of the quality of MacromdiaFlash 8 Professional that was developed. This study is a development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were class IV C students in a small group trial of 10 students and class IV B students in a large group trial. Techniques for collecting expert data collection (media experts, learning experts, material experts), on product trials using teacher assessment questionnaires and student responses as suggestions and input for the feasibility of MacromediaFlash 8 Professional Based on Love Characters Homeland that researchers developed. The results of the study showed that the assessment of media experts received a 77.7 score in the category "Eligible". Assessment of learning experts received a score of 86.5 with the category "Very Worthy". The assessment of material experts scored 81.6 with the "Very Worthy" category. In evaluating product trials (small groups) scored 91.85 in the "Very Worthy" category. In the assessment of usage trials (large groups) scored 91.60 in the "Very Worthy" category. The conclusion of use.